Association of Hepatic Steatosis With Major Adverse Cardiovascular Events, Independent of Coronary Artery Disease - Meyersohn, Nandini M.; Mayrhofer, Thomas; Corey, Kathleen E.; Bittner, Daniel O.; Staziaki, Pedro V.; Szilveszter, Balint; Hallett, Travis; Lu, Michael T.; Puchner, Stefan B.; Simon, Tracey G.; Foldyna, Borek; Voora, Deepak; et al. (Clinical Gastroenterology and Hepatology, 2021)
Background & Aims: Hepatic steatosis has been associated with increased risk of major adverse cardiovascular events (MACE) but it is not clear whether steatosis is independently associated with risk of MACE. We investigated whether steatosis is associated with risk of MACE independently of the presence and extent of baseline coronary artery disease, assessed by comprehensive contrast-enhanced computed tomography angiography (CTA). Methods: We conducted a nested cohort study of 3756 subjects (mean age, 60.6 years; 48.4% men) who underwent coronary CTA at 193 sites in North America, from July 2010 through September 2013, as part of the PROMISE study, which included noninvasive cardiovascular analyses of symptomatic outpatients without coronary artery disease. Independent core laboratory readers measured hepatic and splenic attenuation, using non-contrast computed tomography images to identify steatosis, and evaluated coronary plaques and stenosis in coronary CTA images. We collected data on participants’ cardiovascular risk factors, presence of metabolic syndrome, and body mass index. The primary endpoint was an adjudicated composite of MACE (death, myocardial infarction, or unstable angina) during a median follow-up time of 25 months. Results: Among the 959 subjects who had steatosis (25.5% of the cohort), 42 had MACE (4.4%), whereas among the 2797 subjects without steatosis, 73 had MACE (2.6%) (hazard ratio [HR] for MACE in subjects with steatosis, 1.69; 95% CI, 1.16–2.48; P = .006 for MACE in subjects with vs without steatosis). This association remained after adjustment for atherosclerotic cardiovascular disease risk scores, significant stenosis, and metabolic syndrome (adjusted HR, 1.72; 95% CI, 1.16–2.54; P = .007) or obesity (adjusted HR, 1.75; 95% CI, 1.19–2.59; P = .005). Steatosis remained independently associated with MACE after adjustment for all CTA measures of plaques and stenosis. Conclusions: Hepatic steatosis is associated with MACE independently of other cardiovascular risk factors or extent of coronary artery disease. Strategies to reduce steatosis might reduce risk of MACE. ClinicalTrials.gov no: NCT01174550
CRIS-Team Scopus Importer:2021-06-25
Keywords: CT; Heart Disease; MAFLD; NAFLD